2021
DOI: 10.1037/men0000276
|View full text |Cite
|
Sign up to set email alerts
|

Men’s stress expression and perception of partner’s support within the romantic relationships: A systematic review.

Abstract: Although research on men's stress expression, coping strategies, and attitudes toward support has been accumulated, there is a lack of evaluation of men's stress expression and perception of their partners' supportiveness within the context of romantic relationships. This review summarizes findings related to factors that influence men's expression of stress and the ways in which they perceive the support provided by their romantic partners, as well as the resulting effects on men's well-being and that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…First, sex may enhance the bond between partners and increase satisfaction with social interactions, which can lead to stronger social support. For example, Kapsaridi and Charvoz’s review found that men in strong romantic relationships had stronger social support, helping them manage stress and other relationships [ 52 ]. Second, according to self-determination theory, engaging in sex for pleasure is an intrinsic motivation that satisfies individual needs and increases relationship well-being [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, sex may enhance the bond between partners and increase satisfaction with social interactions, which can lead to stronger social support. For example, Kapsaridi and Charvoz’s review found that men in strong romantic relationships had stronger social support, helping them manage stress and other relationships [ 52 ]. Second, according to self-determination theory, engaging in sex for pleasure is an intrinsic motivation that satisfies individual needs and increases relationship well-being [ 53 ].…”
Section: Discussionmentioning
confidence: 99%